Curie point singularity in the temperature derivative of resistivity in (Ga,Mn)As - Novák, V; Olejník, K; Wunderlich, J; Cukr, M; Výborný, K; Rushforth, A W; Edmonds, K W; Campion, R P; Gallagher, B L; Sinova, Jairo; Jungwirth, T (Physical review letters, 2008)
We observe a singularity in the temperature derivative drho/dT of resistivity at the Curie point of high-quality (Ga,Mn)As ferromagnetic semiconductors with Tc's ranging from approximately 80 to 185 K. The character of the anomaly is sharply distinct from the critical contribution to transport in conventional dense-moment magnetic semiconductors and is reminiscent of the drho/dT singularity in transition metal ferromagnets. Within the critical region accessible in our experiments, the temperature dependence on the ferromagnetic side can be explained by dominant scattering from uncorrelated spin fluctuations. The singular behavior of drho/dT on the paramagnetic side points to the important role of short-range correlated spin fluctuations.